Strategi Pembentukan Akhlak Mulia Murid-Murid di SD Islam Sjech M. Djamil Djambek Bukittinggi - Erlina Erlina; Dewi Angraini; Husnaini Rahmi Arrumi (STIKes Ibnu Sina Ajibarang, 2024)
This study examines the strategy of forming noble character in SD Islam Sjech M. Djamil Djambek Bukittinggi through a qualitative case study approach. The results of the study indicate the success of integrating Islamic values ​​into the curriculum, habituation of religious culture, and school-family-community synergy. These findings emphasize the importance of a holistic approach in character education. Recommendations are given for strengthening collaborative models in the digital era.